Pharmacokinetics, Bioequivalence, and Safety of Esomeprazole Magnesium Enteric‐Coated Capsules in Healthy Chinese Subjects - Jin, Juan; Huang, Cuiping; Zhu, Changhai; Feng, Wanni; He, Ang; Li, Tuo; Wang, Lina; Wang, Xiaolu; Rao, Xiali; Gan, Fangliang (Clinical pharmacology in drug development, 2023)
This bioequivalence study is critically important for drug production. Recently, a local pharmaceutical company produced esomeprazole magnesium enteric‐coated capsules, a major drug to help to eradicate Helicobacter pylori, but the bioequivalence is not well known. The present study aimed to evaluate the bioequivalence of the 2 esomeprazole magnesium enteric‐coated capsules and their pharmacokinetics and safety in 3 biological equivalence trials: fasting, feeding, and mixing. The fasting and mixing trials used single‐centered randomized, open‐label, single‐dose, 2‐treatment, 2‐period, and 2‐sequence crossover design, while the fed trials used single‐centered, randomized, open‐label, single‐dose, 2‐treatment, 3‐period, 3‐sequence partial crossover design. For the fasting and mixing trials, each of the 32 subjects was fasted overnight prior to taking the test preparations or reference preparations. In the fed trial, 54 subjects were given a high‐fat meal 1 hour before the drugs were administered. Blood specimens from all subjects were collected against the light within 14 hours, with the plasma drug concentration being detected by the validated ultra‐performance liquid chromatography–tandem mass spectrometry analysis method. Geometric mean ratio of maximum concentration, the area under the concentration–time curve from time zero to the last measurable concentration, and area under the concentration–time curve from time zero to infinity with 90% confidence interval were calculated. The data from fasting, mixing, and fed trials met the bioequivalence criteria. No serious adverse reactions were found, suggesting that the test and reference preparations of esomeprazole magnesium enteric capsules have similar safety profile.